1998
DOI: 10.1016/s0014-5793(98)00977-6
|View full text |Cite
|
Sign up to set email alerts
|

Density‐ and proliferation status‐dependent expression of T‐cadherin, a novel lipoprotein‐binding glycoprotein: a function in negative regulation of smooth muscle cell growth?

Abstract: The atypical low density lipoprotein (LDL) binding proteins (M r 105 and 130 kDa ; p105 and p130) in human aortic medial membranes and cultured human and rat aortic smooth muscle cells (SMC) have recently been identified as the cell adhesion glycoprotein T-cadherin. Although cadherins are generally recognized to be important regulators of morphogenesis, the function of T-cadherin in the vasculature is poorly understood. This study has examined the relationship between expression of T-cadherin and the density a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…These results suggested that T-cadherin expression might be regulated by culture conditions in vitro. Previous studies have demonstrated that growth factors, confluence, and serum deprivation all modulate T-cadherin expression in other cell types (37). Similar to these results, we found that T-cadherin expression increases in primary astrocytes in vitro in response to conditions that promote growth arrest (serum starvation and contact inhibition).…”
Section: Discussionsupporting
confidence: 90%
“…These results suggested that T-cadherin expression might be regulated by culture conditions in vitro. Previous studies have demonstrated that growth factors, confluence, and serum deprivation all modulate T-cadherin expression in other cell types (37). Similar to these results, we found that T-cadherin expression increases in primary astrocytes in vitro in response to conditions that promote growth arrest (serum starvation and contact inhibition).…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, T-Cad can also function as a receptor for low density lipoprotein and adiponection/Acrp30 (26,27). T-Cad is down-regulated by growth factors such as IGF, EGF, and bDGF in smooth muscle cells (28). The molecular mechanism for its down-regulation by these growth factors has not been elucidated.…”
mentioning
confidence: 99%
“…Immunoblotting of whole cell lysates was performed as described previously. 33 The following primary antibodies were used: rabbit antiphospho thr202/tyr204 -ERK1/2, rabbit antiphospho ser473 -Akt, rabbit antiphospho thr180/tyr182 -p38MAPK (Cell Signaling Technology) and goat anti-GAPDH (Abcam, UK) as the internal protein loading control. Secondary HRP-conjugated goat antirabbit IgG (Southern Biotechnology) or donkey antigoat IgG (Santa Cruz Biotechnology) together with Amersham ECL (Amersham Biosciences, UK) were used to detect immunoreactive proteins.…”
Section: Western Blottting (Wb)mentioning
confidence: 99%